A new groundwater-dwelling species of Euryrhynchina from Cameroon (Malacostraca, Decapoda, Euryrhynchidae) - De Grave, S; Piscart, C; Kayo, R; Anker, A (Magnolia Press, 2017)
A new species of the euryrhynchid shrimp genus Euryrhynchina Powell, 1976, E. puteola sp. nov., is described from Cameroon. The new species can be easily distinguished from the only other species in the genus, E. edingtonae Powell, 1976, by the absence of a setiferous lobe on the eye peduncle, the absence of a meral spine on the ambulatory pereiopods, the shape of the scaphocerite tooth, a single spine on the uropodal diaeresis (vs. 2–3), the absence of a podobranch on the second maxilliped, and the absence of appendices internae on the male pleopods 2-5. Although the species was discovered in a phreatic well, it remains unclear if it is a true stygobiont.